2018
DOI: 10.1016/j.ehj.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute coronary syndrome in patients below the age of 40 years

Abstract: BackgroundAcute coronary syndrome (ACS) refers to a spectrum of symptoms compatible with acute myocardial ischemia. Plasma markers of inflammation have been recently identified as diagnostic aid and risk predictors. The present study, conducted in Slemani Cardiac Hospital (SCH), Sulaimaniyah, Iraq aimed to recognize some risk factors for ACS in Iraqi adults younger than 40.MethodologyThis is a prospective case-control study of 100 patients with ACS vs. a control group of 100 healthy volunteers. The study began… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
32
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 10 publications
5
32
0
4
Order By: Relevance
“…They concluded that obesity, smoking, number of diseased vessels, hypertension, family history of ACS, and diabetes mellitus were, sequentially, the most frequent risk factors for ACS. 30 This finding is also in line with many other previously conducted studies that have referred to smoking, hypertension, diabetes, obesity, and dyslipidemia as risk factors for the development of ACS. [31][32][33][34] Chest pain has been introduced as the most common presentation of an ACS.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They concluded that obesity, smoking, number of diseased vessels, hypertension, family history of ACS, and diabetes mellitus were, sequentially, the most frequent risk factors for ACS. 30 This finding is also in line with many other previously conducted studies that have referred to smoking, hypertension, diabetes, obesity, and dyslipidemia as risk factors for the development of ACS. [31][32][33][34] Chest pain has been introduced as the most common presentation of an ACS.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in good agreement with previous studies that have referred to male gender as a risk factor for ACS. 26,[28][29][30] Hypertension was found to be the most frequent risk factor among the studied AMI patients, such that 65 cases (54.4%) had hypertension. Other most frequent risk factors were observed to be dyslipidemia (52%), smoking (42.4%), diabetes mellitus (38.4%), obesity (24%), family history (14.4%), and physical inactivity (3.2%).…”
Section: Discussionmentioning
confidence: 85%
“…In order to provide earlier and better diagnosis of CAD in young adults, novel risk factors and markers have been evaluated in the literature [6][7][8]. However, these studies included specific cohorts, such as ACS [6][7][8][9]. Therefore, we aimed to investigate the relationship between traditional and nontraditional risk factors and the presence of significant atherosclerosis in a young population with SAP.…”
Section: Introductionmentioning
confidence: 99%
“…Even though ischemic heart disease is considered a disease of the older population 7 premature CAD remains a signifi cant cause of morbidity and mortality in the world. 8 AMI in the young individuals represent a small but yet an important group to study its specifi cities in the era of preventive cardiology.…”
Section: Discussionmentioning
confidence: 99%